Diffusion and hydrolysis effects during water aging on an epoxy-anhydride system - Capiel, Guillermina (2018)
Hydrothermal aging of an epoxy-anhydride network has been studied by means of gravimetric analysis, Fourier transform infrared spectroscopy (FTIR) and modulated differential scanning calorimetry (MDSC). The long-term aging results revealed a fourth stage mechanism in which an initial short diffusional period is followed by the hydrolysis of the ester groups. Degraded materials showed two values of glass transition temperature suggesting a heterogeneous process. Hydrolysis undergoes in preferential sites due to the catalytic effect of the carboxyl acids formed during the chemical degradation. Domains with low crosslinking density and high mobility are formed. At long degradation time, samples presented a unique glass transition temperature around 50 °C. The lixiviation of low molecular weight species formed by the hydrolytic scissions was confirmed by FTIR and pH variations.